Halal Laundry Detergents: Ingredients and Regulations in Malaysia - Nur Azira Tukiran; Raihanah Badrul Hisham (Halalsphere, 2024)
Cleaning products are necessary for our daily lives since they are highly effective in cleaning and washing. They assist in personal hygiene by loosening and removing soil and dirt from the surface, diminishing germs or bacteria that are the source of infectious diseases and making the surroundings comfortable. There are three most common detergents in various places: laundry, dishwashing, and household cleaning. Hence, this review paper focuses on laundry detergent to clean the dirt on fabrics and clothes. This paper aims to provide general knowledge for consumers, particularly Muslims, of the ingredients used in laundry detergents and the halal-related regulations in Malaysia. Ingredients used in detergent products, such as enzymes derived from animals, plants, fungi, and bacteria, have issues with where the sources were obtained, which subsequently become one of the reasons many productions have issues fulfilling the halal certification requirement. Other than enzymes, many other ingredients are added to detergent products to provide specific properties and characteristics, such as surfactants, builders, alkalis, bleaches, colourants, and fragrances, which consumers should know before purchasing. Manufacturers must inform Muslim consumers about the purity and impurity of the ingredients used in laundry detergents to make wise decisions in purchasing halal products.